2015
DOI: 10.1007/s12094-015-1323-x
|View full text |Cite
|
Sign up to set email alerts
|

The differences of clinicopathological factors for breast cancer in respect to time of recurrence and effect on recurrence-free survival

Abstract: Clinicopathological factors predicting the recurrence time in breast cancer were important to modify adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Despite this increase in survival, women diagnosed with BC, and treated with surgery plus adjuvant therapy have a recurrence risk of 5%–13% [ 4 , 5 ]. Tumor size and axillary lymph node metastasis are the most relevant risk factors for tumor relapse [ 6 , 7 ]. The primary means for reducing recurrence is medical intervention (e.g., chemotherapy, radiation, and endocrine treatment) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this increase in survival, women diagnosed with BC, and treated with surgery plus adjuvant therapy have a recurrence risk of 5%–13% [ 4 , 5 ]. Tumor size and axillary lymph node metastasis are the most relevant risk factors for tumor relapse [ 6 , 7 ]. The primary means for reducing recurrence is medical intervention (e.g., chemotherapy, radiation, and endocrine treatment) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the relationship between the degree of tumor malignancy and TTR, Fujii et al [21] showed that a lower pathological T stage was significantly more common in the late-recurrence group (after 5 years from resection) than in the early-recurrence group (within 5 years from resection) in patients with renal cell carcinoma. Oven et al [22] also showed a similar tendency in breast cancer patients. Consistent with these previous studies, our study showed that tumors with low mitotic count were significantly more common in the L-group.…”
Section: Discussionmentioning
confidence: 66%
“…Disease extent in patients with metastatic breast cancer is highly variable, ranging from solitary bone metastasis to widespread bone marrow involvement, and often including extra-skeletal sides such as lung, pleura, liver and lymph nodes [ 18 ]. Thus, survival of these patients might vary from few months to several years.…”
Section: Discussionmentioning
confidence: 99%